2018
DOI: 10.35580/bionature.v18i2.6146
|View full text |Cite
|
Sign up to set email alerts
|

Respon Pertumbuhan Jagung (Zea mays) Dengan Pemberian Urea Bersalut Zeolit Sebagai Nitrogen Lepas Lambat

Abstract: This study is an experimental research that aims to find out how the response of corn growth (Zea mays) with urea-coated zeolite as nitrogen release slowly, implemented from April to December 2017. The making of fertilizer is done in The corn variety used was HJ 21 Agritan. Observation parameters were stem circumference, leaf chlorophyll content, plant biomass (root, stem and leaves), cob weight, ear length, seed weight, leaf nitrogen and seed nitrogen. The technique of data origin is done by using variance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Urea fertilizer is a fertilizer containing 45-46% N, is very soluble in water and reacts quickly, is also easily converted into ammonium ions (NH4 +) that can be absorbed by plants (Sutedjo, M. M., 2002). This is in agreement Nur Aina et al, 2017) states that in good environmental conditions to carry out photosynthesis can produce (60-80)% of the assimilate results are translated into other plants in the organs of growth and production. Growth and production will increase if supported by environmental factors such as light and water (Bunyamin and Aqil, 2009), (Heard, J., 2004) but at the time of this study, water could not need to be fulfilled because at the time of this study it coincided with the start of the dry season when the plant growth phase had a lack of water, so the growth and production of plants do not get maximum results.…”
Section: The Effect Of the Using Urea Doses On The Growth Of Corn Cropsupporting
confidence: 90%
See 1 more Smart Citation
“…Urea fertilizer is a fertilizer containing 45-46% N, is very soluble in water and reacts quickly, is also easily converted into ammonium ions (NH4 +) that can be absorbed by plants (Sutedjo, M. M., 2002). This is in agreement Nur Aina et al, 2017) states that in good environmental conditions to carry out photosynthesis can produce (60-80)% of the assimilate results are translated into other plants in the organs of growth and production. Growth and production will increase if supported by environmental factors such as light and water (Bunyamin and Aqil, 2009), (Heard, J., 2004) but at the time of this study, water could not need to be fulfilled because at the time of this study it coincided with the start of the dry season when the plant growth phase had a lack of water, so the growth and production of plants do not get maximum results.…”
Section: The Effect Of the Using Urea Doses On The Growth Of Corn Cropsupporting
confidence: 90%
“…The yield in the form of seeds of urea fertilizer is best using 6.3 g / plant (150 kg/ha), according to the results of the study Nur Aina et al (2017) that the recommended dosage for growth and production of 150 kg/ha corn plants is slightly lower which is planted in the highlands with a recommendation of 4.2 g / plant (U2). Based on the use of the higher dose of urea fertilizer given to plants is the availability of elements in growth, this is by the opinion (Kresnatita S. et el.…”
Section: The Effect Of the Using Urea Doses On The Corn Croppingmentioning
confidence: 99%
“…The use of zeolite will increase water storage capacity and cation exchange capacity so that N-ammonium nutrients can be stored. Experiments carried out by Aina et al (2017) showed that the use of zeolite in corn plantations could increase the biomass of corn plants cultivated using NPK. Another experi- The application of nitrogen fertilizer at all doses (75, 100, and 125 kg per hectare) without zeolite treatment produced the lowest weight of fresh biomass compared to other treatment combinations.…”
Section: Resultsmentioning
confidence: 99%
“…The use of nano zeolite yielded the best results (Figure 5) because zeolite contains a cavity that corresponds to the size of the ammonium ion, resulting in a high ammonium adsorption capacity. The use of zeolite as a zeolitecoated urea coating with a concentration of 10% gave the highest cob weight and cob length (Aina and Jumadi, 2018).…”
Section: Shoot Fresh and Dry Weightmentioning
confidence: 99%